Strategi Pengembangan Destinasi Wisata Museum Sejarah Jakarta Pasca Pandemi Covid – 19 - Rizki Nurul Nugraha; Tarabunga Angelyca (Jurnal Ilmiah Wahana Pendidikan, 2023)
Indonesia announced its first case of COVID-19 on March 2 2020, and on March 11 2020 WHO announced that COVID-19 was a pandemic outbreak because it had surpassed the SARS epidemic in 2003, so several countries imposed lockdowns and travel restrictions sequentially. This has caused the cessation of all tourist activities, one of which is the Jakarta History Museum. The purpose of this study is to identify the development strategy carried out by the managers of the Jakarta History Museum after the Covid-19 pandemic. The analysis techniques in this study are interviews, observation and SWOT analysis approaches. Based on the results of interviews and SWOT analysis, the management has made efforts to develop and increase tourists visiting the Jakarta History Museum tourist destination. The results of the study concluded that post-pandemic development of the Jakarta History Museum tourist destination is very important to note in maintaining the continuity of tourism activities in tourist destinations. Several suggestions were given to managers, one of which was to develop a more interactive museum collection facility.